2022
DOI: 10.22487/agroland.v9i2.1445
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Dominance of Plankton in Pond Waters of South Banawa District After the 2018 Earthquake

Abstract: South Banawa District is one of the areas in Donggala Regency which has the best prospects in the pond aquaculture sector because this area has the potential to produce milkfish and shrimp. The earthquake and tsunami of 28 September 2018 damaged most of the ponds in South Banawa District. This study aimed to analyze the composition, diversity, and dominance of plankton in fish and shrimp farming ponds in Lalombi and Tolongano Village. The diversity index (H ́) of plankton in the two villages, namely Lalombi, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The application of seaweedbased fertilizers has demonstrated improved productivity in various crops, including tomato, sugarcane, maize, wheat, and paddy [6][7][8][9][10]. Generally, seaweed contains essential minerals such as irone, iodine, manganese, calcium, nitrogen, phosphorus, sulphur, boron, potassium, and other elements which are essential to support plant growth [11]. Our previous work has also shown that supplementation of brown seaweed Sargassum-based fertilizer could increase growth and rice productivity and nutritional quality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The application of seaweedbased fertilizers has demonstrated improved productivity in various crops, including tomato, sugarcane, maize, wheat, and paddy [6][7][8][9][10]. Generally, seaweed contains essential minerals such as irone, iodine, manganese, calcium, nitrogen, phosphorus, sulphur, boron, potassium, and other elements which are essential to support plant growth [11]. Our previous work has also shown that supplementation of brown seaweed Sargassum-based fertilizer could increase growth and rice productivity and nutritional quality [12,13].…”
Section: Introductionmentioning
confidence: 99%